THE IMPACT OF KNOWLEDGE MANAGEMENT PROCESSES ON INFORMATION SYSTEMS: AN EMPIRICAL STUDY ON IT INDUSTRY - V, Ms. Jalaja; Bhatt, Ms. Himresha (The journal of contemporary issues in business and government, 2022)
The Information Technology sector has been profoundly impacted by advances in project management knowledge. As a result, it is critical to optimize service development processes in every project. This article focuses to explore the composition of “ Knowledge Management” of IT professionals. The current research proposes a model of the impact of Management Support for Knowledge Application on Project Knowledge Application and Project Knowledge Application on effective Knowledge Management in the IT industry. To conduct the current analysis, the researchers used a quantitative research approach in the form of a survey. The questionnaire was randomly distributed to 180 IT employees of various software companies. The researchers did, however, collected 165 completed questionnaires and Reliability test, EFA and Simple Linear Regression statistical methods used. It is found that that there is a positive correlation between Project Knowledge Application and Effective Knowledge Management in IT Industry professionals.